Interaction between methadone and clarithromycin as the suspected cause of an opioid toxidrome. Issue 5 (25th May 2021) - Wallace, Blair; Edwardes, Daniel; Subbe, Christian; Murtaza, Muhammed
Abstract : A 40-year-old patient was admitted through the acute medical take with pleuritic chest pain and rigours. He had a medical history of opiate dependence and was receiving 60 mg of methadone once daily. He was diagnosed with a community-acquired pneumonia and treated with amoxicillin and clarithromycin. After administration of only two concomitant doses of methadone and oral clarithromycin, he developed an opioid toxidrome with type-2 respiratory failure, a decreased level of consciousness and pinpoint pupils. The patient was treated with naloxone and his symptoms improved. Retrospectively, it was suspected that an interaction between clarithromycin and methadone might have contributed to the toxidrome. Respiratory failure has not been previously prescribed for this combination of medication and is of high importance for physicians and pharmacists around the world.